Pengaruh Return on Asset, Return on Equity dan Earning Per Share Terhadap Harga Saham Perusahaan LQ-45 Yang Terdaftar di Bursa Efek Indonesia Periode 2021 - Yulistia Husnaini (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine whether Return on Assets, Return on Equity, and Earning Per Share have an effect simultaneously or partially on stock prices in LQ-45 companies listed on the Indonesia Stock Exchange. The approach used in this research is a quantitative approach. The population used in this study were 45 companies and used a saturated sample. Documentation technique is used as a data collection technique in this study and the data source used is secondary data published by the company on the official website of the Indonesia Stock Exchange www.idx.co.id. The data analysis technique used is multiple linear regression analysis using SPSS version 25. The results of this study indicate that simultaneously Return on Assets, Return on Equity, and Earning Per Share have a significant effect on stock prices. Partially, Return on Assets has no significant effect on stock prices. Return On Equity partially has a significant effect on stock prices. Earning Per Share partially has no significant effect on the stock price.